P139 What threshold of total sleep time of hypercapnia should define hypoventilation in children with neuromuscular disorders?. (9th November 2022) - Withers, A; Wilson, A; Downs, J; Jacoby, P; Hall, G; Gauld, L; O'Donnell, A; Chacko, A; Schultz, A
Abstract: Background: there are numerous definitions of hypoventilation, the most commonly used for children being pCO₂ >50mmHg >25% total sleep time. There are concerns that a total sleep time threshold of >25% is not sensitive enough in children and individuals with neuromuscular disorders. Alternative thresholds of 2%, 5% and 10% total sleep time have been suggested. Methods: the relationship between percentage of total sleep time with pCO₂ >50mmHg and the presence of hypoventilation (determined by physician diagnosis) was examined in a small exploratory analysis of children with neuromuscular disorders. ROC curves were constructed to determine the impact of changing cut-off thresholds for total sleep time with pCO₁ >50mmHg to define hypoventilation. Results: the mean percentage of total sleep time that pCO₂ >50mmHg was higher for the studies with hypoventilation (50% vs.10%). The mean difference (40%) was not statistically significant, likely due to the small number of studies (n=6) with hypoventilation. The AUC for percentage of total sleep time with pCO₂ >50mmHg was 0.808 (p=0.035, CI 0.6 to 1.0). For thresholds of total sleep time with pCO₂ >50mHg to define hypoventilation of 20% and 27%, sensitivity was 50%. For thresholds of 11%, 5% and 3%, sensitivity was 67%, 100% and 100% respectively. Conclusions: in this study the upper limit of total sleep time with pCO₂ >50mmHg in children with neuromuscular disorders without hypoventilation was 10%. Thresholds lower than 25% of total sleep time with pCO₂ >50mmHg to define hypoventilation had higher sensitivity for diagnosing hypoventilation in this population.